The effects of endocannabinoids and phytocannabinoids on bronchial epithelial permeability - Shang, Valerie C.M. (2016)
Injury to the bronchial epithelium in respiratory diseases such as asthma and COPD results in the loss of barrier function and an elevated sensitivity to environmental insults. An increased release of the endogenous cannabinoid, anandamide in response to inhalation of allergen in asthmatic patients has been reported. In contrast, previous clinical trial findings suggest anti-inflammatory and broncho-relaxant properties of the phytocannabinoid, ∆9-tetrahydrocannabinol (THC). The aim of this study was, therefore, to determine the effects of endocannabinoids and phytocannabinoids on bronchial epithelial cell permeability and to investigate the mechanisms involved. Calu-3 human bronchial epithelial cells were cultured at air-liquid interface to allow development of tight junctions. Changes in transepithelial electrical resistance (TEER), a reflection of epithelial permeability, were measured at various time points post-treatment. The endogenous cannabinoid anandamide produced a significant reduction in TEER, which was unaffected by cannabinoid receptor antagonists, but attenuated by URB597, an inhibitor of fatty acid amide hydrolase, and by a combination of cyclooxygenase and lipooxygenase blockade. Subsequent immunoblotting data revealed that the expression of tight junction proteins, occludin and ZO-1, were also reduced by anandamide. Inhibition of ERK activation by MEK1/2 inhibitors, PD98059 and U0126, prevented the anandamide-induced reduction in TEER and prevented the reduction in occludin expression. Thus, ERK activation is likely to mediate these effects by altering the expression of tight junction proteins. Treatment with THC prevented TNFα-induced decrease in TEER and increased in paracellular permeability. CB1 and CB2 receptor-like immunoreactivity was found in Calu-3 cells. Subsequent pharmacological blockade of either cannabinoid receptor inhibited the THC effect. In comparison, stimulation of both or either CB1 or CB2 receptors displayed similar effect to that of THC. Western immunoblotting also revealed reproducible decreases in occludin and ZO-1 expression in TNFα-treated cells, whereas cells pre-incubated with THC alone or in combination with TNFα did not alter expression levels. Phosphorylation of myosin-phosphatase target protein at threonine 696 residue by TNFα was attenuated in the presence of THC, indicating the involvement of RhoA/ROCK cascade. Selective stimulation of either cannabinoid receptor in TNFα-treated cells suggests THC-induced inhibitory effect on RhoA/ROCK signalling was mediated through CB2 receptor, and not CB1. In summary, these data suggest that the reduction in transepithelial resistance by anandamide, indicative of increased epithelial permeability, is caused by its metabolites rather than anandamide itself. Inhibition of anandamide degradation might provide a novel approach to treat airway inflammation. Conversely, THC reverses the reduction in transepithelial resistance caused by TNFα, through an effect at CB1 and CB2 receptors. Hence, THC, or perhaps other cannabinoid receptor ligands may have potential therapeutic roles in inflammation-induced changes in airway epithelial cell permeability, such as asthma and COPD.